Effects of whole-body vibration on flexibility and stiffness: A literature review - Fowler, B.; Palumbo, T.; Feland, B.; Blotter, J. (International Journal of Exercise Science, 2019)
The effects of whole-body vibration (WBV) on flexibility and muscle stiffness are focused areas of research. Many studies have been performed over a large range of vibratory conditions and have reported varied results on effectiveness. When reviewing the published literature, it is difficult to track the vibration parameters that have positive effects and which have negative or no effects. In writing this paper,over 80 articles were evaluated, 24 of which met the inclusion requirements. The data gathered in the articles were used to develop charts that illustrate the vibration conditions that elicit helpful, harmful, and no effects on flexibility and muscle stiffness. A combination of published data shows that acceleration is the best metric to predict the effectiveness of WBV for improving flexibility and muscle stiffness. This review shows that acceleration in the range of 5g to 10g was most effective in increasing flexibility. Published data on muscle and tendon stiffness are limited, but shows that although WBV is generally significantly less effective in increasing stiffness than increasing flexibility, accelerations below 6.4g were the most effective.